1995
DOI: 10.1002/micr.1920160905
|View full text |Cite
|
Sign up to set email alerts
|

Use of ultrasonography to evaluate muscle thickness and blood flow in free flaps

Abstract: The purpose of this study was to investigate the common belief that a microvascular transfer of a non-innervated free muscle flap loses muscle bulk over time. Sixteen patients (latissimus dorsi = 8, rectus abdominis = 7, and gracilis muscle = 1) were evaluated an average of 41 months after free flap transfer. Latissimus dorsi and lower extremity flaps displayed significantly more swelling than the other flaps. Flap bulk was measured by ultrasound. The mean thickness of upper extremity flaps was 10.3 +/- 1.8 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

1995
1995
1999
1999

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 27 publications
0
16
0
1
Order By: Relevance
“…They also showed that, in the lower extremity, free muscle flaps maintain their vascular pe-dicle and seem to have more muscle bulk, probably because of vigorous blood flow through their pedicles and in the muscle tissue itself (132). On the other hand most pedicles could not be found by ultrasound examination in free muscle flaps transplanted to the upper extremity (132). Machens et al found persistence of pedicle blood flow for up to 10 years after uncomplicated free LD transfer (93) whereas loss of autonomous blood supply through the vascular pedicle, with thrombosis of the venous anastomosis, seems to occur in free tissue transfers even after successful surgical revision (92).…”
Section: Free Muscle Flapsmentioning
confidence: 99%
See 4 more Smart Citations
“…They also showed that, in the lower extremity, free muscle flaps maintain their vascular pe-dicle and seem to have more muscle bulk, probably because of vigorous blood flow through their pedicles and in the muscle tissue itself (132). On the other hand most pedicles could not be found by ultrasound examination in free muscle flaps transplanted to the upper extremity (132). Machens et al found persistence of pedicle blood flow for up to 10 years after uncomplicated free LD transfer (93) whereas loss of autonomous blood supply through the vascular pedicle, with thrombosis of the venous anastomosis, seems to occur in free tissue transfers even after successful surgical revision (92).…”
Section: Free Muscle Flapsmentioning
confidence: 99%
“…Using magnetic resonance imaging (MRI), computer assisted tomography (CT) and colour Doppler ultrasound, Salmi et al showed in clinical studies that the extensive postoperative swelling of a free muscle flap subsides over time and that the flap regains its original thickness in 6-9 months (133,134) although lower extremity and LD muscle flaps tend to be thicker (132). They also showed that, in the lower extremity, free muscle flaps maintain their vascular pe-dicle and seem to have more muscle bulk, probably because of vigorous blood flow through their pedicles and in the muscle tissue itself (132).…”
Section: Free Muscle Flapsmentioning
confidence: 99%
See 3 more Smart Citations